A Life-Cycle Framework for Managing Risks in Public Private Partnership Housing Projects - Yakubu N. Sanda; Natalia A. Anigbogu; Lura Y. Nuhu; Ola S. Olumide (Journal of Engineering, Project, and Production Management, 2020)
Public private partnership projects have been adjudged to contain more risks than traditionally procured projects due to more number of parties involved and their varying interests. These risks affect the achievement of projects objectives and therefore need to be identified and treated to guarantee project success. This paper developed a life cycle framework for managing risks in PPP housing projects in Nigeria. The respondents were selected using purposeful sampling technique. The data used for the study were obtained through semi-structured questionnaire and were analysed using mean rating. Risk transfer was found to be the widely used measure for responding to risks in PPP housing projects. The criteria mostly used for risk allocation were party with the best ability to manage specific risks should they occur and ability of the party to foresee risks. A four-stage life cycle framework was developed, evaluated and validated by experts in the built environment to ascertain its reliability. The framework is recommended for PPP housing projects in Nigeria.